Evaluation of the National Adherence Guidelines for Chronic Diseases in South Africa : The Impact of Differentiated Care Models on Short-Term Indicators in HIV Patients - World Bank (World Bank, Washington, DC, 2018)
This report describes the short-term outcomes of an evaluation study for five different HIV cohorts using routinely collected data. The evaluation study is a collaboration between the National Department of Health of South Africa, the National Health Laboratory Service (NHLS) and the World Bank. Boston University/Health Economics and Epidemiology Research Office (HE2RO) is the academic partner in the evaluation. The overall aims of the evaluation are to assess the impact of South Africa`s Adherence Guideline interventions on HIV patients’ treatment outcomes; estimate the costs of the interventions; and describe the cascade of care for TB, hypertension, and diabetes at the same clinics. The short-term endpoints reported on herein concern ART initiation among FTIC eligible patients, ARV medication pick-up among AC and DMD eligible patients, retention in care among TRIC eligible patients, and viral load suppression among EAC eligible patients. The final outcomes of this evaluation will be reported on separately, once patients have been follow-up for one year and routine data on viral load suppression and retention in care become available